The Core of Pure Economic Loss - Guiseppe Dari-Mattiacci; Hans-Bernd Schäfer (Tinbergen Institute, 2006)
Should loss of earnings be compensated? The established law and economics wisdom considers pure economic loss as a transfer of wealth from the victim to a third party, whose earnings increase as a consequence of the accident. Such transfers do not amount to a social loss and, hence, should not be compensated. We revisit these arguments and show that the social loss should be calculated by taking into account that: (a) pure economic loss often involves impairment costs resulting from the fact that valuable resources cannot be temporarily used; and (b) the third-party earnings come at the cost of increased capacity. This increased capacity mitigates the expected harm and, hence, is a form of precaution. By taking into account these factors, we show that most pure economic loss cases do result in a socially relevant loss. In addition, we argue that the absence of a social loss is a necessary, but not sufficient, condition for the denial of compensation. The victim (or a third party) may have actually paid for protection against purely private losses. Thus, compensation should be awarded irrespective of whether national law treats the case under tort or contract (where compensation is undisputed). Finally, we offer considerations on the optimal design of liability rules.
Keywords: K13; 330; economic loss; financial loss; tort; damage; compensation